(untitled) (The Review of Diabetic Studies, 2025)
Background Quercetin (3,3′,4′,5,7-pentahydroxyflavone) is a naturally occurring flavonoid found in different fruits, vegetables, and drinks. Prevalent dietary sources encompass apples, berries, onions, grapes, broccoli, and tea. This study aims to examine the impact of quercetin administration at dosages of 50 and 100 mg/kg in streptozotocin (STZ)-induced diabetic rats. Material and method The research delineates the procedure for producing diabetes in male Wistar or Sprague-Dawley rats, sanctioned by the Institutional Animal Ethics Committee. Diabetes is caused by a single administration of Streptozotocin (STZ), while precautions are implemented to avert hypoglycemia mortality. Rats are categorized into four treatment groups: a normal control, a diabetic control, one administered Quercetin, and group III receiving standard antidiabetic medications. Blood and liver specimens are obtained post-treatment for the study of glucose, insulin, oxidative stress indicators, and inflammatory cytokines. Results: Quercetin administration in streptozotocin-induced diabetic rats enhanced glycemic regulation and mitigated liver damage and kidney oxidative stress in a dose-dependent manner over eight weeks. Diabetic rats had hyperglycemia, hypoinsulinemia, higher hepatic enzymes, lipid peroxidation, diminished antioxidants, and heightened pro-inflammatory cytokines, signifying significant hepatic injury. Quercetin treatment (50 and 100 mg/kg) restored blood glucose and insulin levels, liver enzyme activity, and inflammation indicators, with the 100 mg/kg dosage producing the most pronounced enhancements. Histological study revealed reduced hepatic degeneration and inflammation, indicating quercetin’s potential as a hepato- and reno-protective drug in diabetes circumstances. Conclusion Quercetin significantly lowers fasting blood glucose, boosts insulin levels, and reduces liver enzymes. It alleviates oxidative stress. Additionally, quercetin reduces inflammation by lowering tumor necrosis factor-alpha and interleukin-6. A dosage of 100 mg/kg improves various health markers, indicating quercetin’s potential in managing diabetes through enhanced insulin sensitivity and hepatoprotective effects.